Family‐centred care interventions for children with chronic conditions: A scoping review - Andrea J. Chow; Ammar Saad; Zobaida Al‐Baldawi; Ryan Iverson; Becky Skidmore; Isabel Jordan; Nicole Pallone; Maureen Smith; Pranesh Chakraborty; Jamie Brehaut; Eyal Cohen; Sarah Dyack; et al. (Wiley, 2024)
Abstract Introduction Children with chronic conditions have greater health care needs than the general paediatric population but may not receive care that centres their needs and preferences as identified by their families. Clinicians and researchers are interested in developing interventions to improve family‐centred care need information about the characteristics of existing interventions, their development and the domains of family‐centred care that they address. We conducted a scoping review that aimed to identify and characterize recent family‐centred interventions designed to improve experiences with care for children with chronic conditions. Methods We searched Medline, Embase, PsycInfo and Cochrane databases, and grey literature sources for relevant articles or documents published between 1 January 2019 and 11 August 2020 (databases) or 7-20 October 2020 (grey literature). Primary studies with ≥10 participants, clinical practice guidelines and theoretical articles describing family‐centred interventions that aimed to improve experiences with care for children with chronic conditions were eligible. Following citation and full‐text screening by two reviewers working independently, we charted data covering study characteristics and interventions from eligible reports and synthesized interventions by domains of family‐centred care. Results Our search identified 2882 citations, from which 63 articles describing 61 unique interventions met the eligibility criteria and were included in this review. The most common study designs were quasiexperimental studies (n = 18), randomized controlled trials (n = 11) and qualitative and mixed‐methods studies (n = 9 each). The most frequently addressed domains of family‐centred care were communication and information provision (n = 45), family involvement in care (n = 37) and access to care (n = 30). Conclusion This review, which identified 61 unique interventions aimed at improving family‐centred care for children with chronic conditions across a range of settings, is a concrete resource for researchers, health care providers and administrators interested in improving care for this high‐needs population. Patient or Public Contribution This study was co‐developed with three patient partner co‐investigators, all of whom are individuals with lived experiences of rare chronic diseases as parents and/or patients and have prior experience in patient engagement in research (I. J., N. P., M. S.). These patient partner co‐investigators contributed to this study at all stages, from conceptualization to dissemination.